Potensi Pangan Fermentasi Tempe dalam Mengatasi Kejadian Malnutrisi - Devina Adira Azzahra; Desi Rahmasari; Hanayu Anindya Nareswari; Margaretha Alesandria Natasya Weka; Rizka Fellithia; Liss Dyah Dewi Arini (Pusat Riset dan Inovasi Nasional, 2025)
Malnutrition remains a significant public health challenge, particularly in developing countries like Indonesia. Tempeh, a fermented soybean product, is highly nutritious and has the potential to address malnutrition. The fermentation process by Rhizopus oligosporus enhances the bioavailability of essential nutrients such as protein, iron, and vitamin B12, which are crucial for growth and development. Additionally, tempeh contains natural prebiotics and probiotics that support digestive health and improve nutrient absorption. A literature review in this study indicates that regular consumption of tempeh can help improve nutritional status, particularly among vulnerable groups such as children and pregnant women. With its affordability and wide availability, tempeh serves as a sustainable food solution that can be optimized to reduce malnutrition rates in Indonesia.